United we stand, divided we fall: antibiofilm activity and mechanisms of action of synthetic peptides in combination with ciprofloxacin against Staphylococcus aureus biofilm - Santos Neto, Nilton Araripe dos (2023)
Staphylococcus aureus is a pathogenic bacterium known as resistant to antibiotics since the mid-20th century and, since then; your resistance did not stop developing resistance, even towards new pharmaceuticals. S. aureus has a huge medical importance, since it is a major organism related to hospital-acquired infections (HAI). Furthermore, S. aureus is capable of forming biofilm, a polymeric extracellular strutcture that confers even more resistance to antibiotics. To overcome this problem, the search for alternative and effective treatments against biofilms of resistant bacteria is necessary. Antimicrobial peptides (AMPs) gained attention as promising alternative molecules, since their mechanisms of action can trespass bacterial resistance mechanisms. Even so, natural AMPs are economically unviable, given their low yield, low stability and toxicity to hosts. As an alternative, synthetic antimicrobial peptides (SAMPs), bioinspired in plant proteins, have been proving advantageous. These synthetic peptides, through punctual modifications into their sequence, can lost their disadvantages like toxicity to host, and can have their antimicriobial activity enhanced. The present work aimed at the analysis of the antibiofilm activity of eight SAMPs, in combination with the antibiotic ciprofloxacin, and elucidate its mechanisms of action through fluorescence microscopy and proteomic analysis. Out of eight, four peptides, in combination with ciprofloxacin, were capable of inhibiting S. aureus biofilm formation up to 76%. The best combination was made by Mo-CBP3-PepIII and ciprofloxacin, and reduced the biomass of preformed biofilm up to 65%, with RcAlb-PepII + ciprofloxacin combination. Fluorescence microscopy analysis revealed that the peptides act by forming pores onto the cell membrane and stimulating reactive oxygen species (ROS) overproduction. In addition, proteomic analysis with the combination of Mo-CBP3-PepI + ciprofloxacin, which achieved 50% of biomass reduction of biofilm, showed an alteration at the proteins profile, especially with proteins related with DNA and protein metabolism, cell wall biosynthesis, redox metabolism, quorum sensing and biofilm formation. Moreover, it was possible to observe a differential accumulation in cells treated with both molecules and cells treated with only one of them, showing a possible synergistic effect.